RISK MANAGEMENT IN INFRASTRUCTURE PROJECT PLANNING: METHODS AND PREVENTIVE STRATEGIES (International Seven Journal of Multidisciplinary, 2023)
Infrastructure projects are inherently exposed to a wide range of uncertainties due to their scale, complexity, long execution periods, and significant financial and social impacts. In this context, risk management plays a critical role in supporting effective planning and decision making, contributing to improved project performance and resilience. This article examines risk management in the planning of infrastructure projects, with a focus on systematic risk identification, qualitative and quantitative risk analysis, and the development of preventive and mitigation strategies. By integrating structured methodologies and analytical tools into the planning phase, project teams can better anticipate potential disruptions, allocate resources more efficiently, and reduce the likelihood and impact of adverse events. The discussion highlights the importance of proactive risk management practices in enhancing cost and schedule predictability, strengthening stakeholder confidence, and increasing the overall probability of project success in complex infrastructure environments.